Planning Scheme for Optimal PMU Location Considering Power System Expansion - Gandhi Carvajal; Diego Carrión; Manuel Jaramillo (Energies, 2025)
In the present research, a methodology was developed for the deployment and optimal location of PMUs with redundancy and system observability constraints at 100%, considering the topological changes generated by transmission expansion planning (TEP). To determine the expansion scenarios and topology changes of the power system, the original IEEE test systems of 14, 30, and 118 buses were used as a starting point, in which a 20-year horizon was considered and an increase in load nodes was proposed, with which the new lines needed were determined by applying TEP. Under these temporal and expansion scenarios, the optimal location of PMUs was determined based on mixed-integer linear optimization, with which the order of location of PMUs was determined. The results of the methodology allow defining the order of PMU implementation in power systems that expand over time.